Freshwater microalgae biomasses exert a prebiotic effect on human colonic microbiota - de Medeiros, Viviane Priscila Barros; de Souza, Evandro Leite; de Albuquerque, Thatyane Mariano Rodrigues; da Costa Sassi, Cristiane Francisca; dos Santos Lima, Marcos; Sivieri, Katia [UNESP]; Pimentel, Tatiana Colombo; Magnani, Marciane (Elsevier, 2021)
The effects of digested microalgae biomass of Chlorella vulgaris, Desmodesmus maximus, Chlorococcum sp. cf hypnosporum, and Spirulina platensis or fructooligosaccharides on human colonic microbiota during in vitro fermentation (48 h) were evaluated. Fructooligosaccharides and digested microalgae biomass increased Lactobacillus-Enterococcus and Bifidobacterium relative abundances and decreased Prevotellaceae-Bacteroidaceae, Clostridium histolyticum, and Eubacterium rectale-Clostridium coccoides. The digested microalgae biomass s showed a higher prebiotic index than fructooligosaccharides, evidenced through the higher selective stimulation of beneficial microorganisms and inhibition of undesirable bacteria on colonic microbiota. S. platensis biomass contained nystose, raffinose, and phenolics, increased the relative abundance of Lactobacillus-Enterococcus and Bifidobacterium, and decreased Eubacterium rectale-Clostridium coccoides, Clostridium histolyticum, and Prevotellaceae-Bacteroidaceae. After 24 h of incubation, the medium fermented with S. platensis promoted an increase in the concentration of acetic and propionic acids. D. maximus biomass showed higher insoluble fibers and kestose, the greatest Lactobacillus-Enterococcus relative abundance, and increases in the butyric and propionic acids after 48 h. C. vulgaris biomass showed the highest glucose and fructose concentrations, some phenolics, and the highest Bifidobacterium relative abundance after 48 h.
Keywords: Freshwater microalgae; Microalgae biomass; Phenolics; Photosynthetic microorganisms; Prebiotic compounds